The molecular identification and characterisation of Eutypa dieback and a PCR-based assay for the detection of Eutypa and Botryosphaeriaceae species from grapevine in South Africa - Safodien, Sieyaam (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.